Aerospace series. Heat resisting alloy NI-PH2601. Solution treated and cold worked. Bar for forged fasteners. D ≤ 50 mm. 1 550 MPa ≤ Rm ≤ 1 830 MPa. (23rd January 2020) - British Standards Institution,
No abstract available